Revising regulations unleashes engineered timber buildings potential for climate mitigation - Sporchia, Fabio; Patrizi, Nicoletta; Ruini, Anna; Bastianoni, Simone (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
Engineered timber can substitute traditional carbon-intense building materials playing a critical role in climate action thanks to its capacity to store biogenic carbon removed from the atmosphere during forest growth. However, the existing regulations and standards developed in the past along with the development of traditional building practices based on concrete and steel, hinder the possibility to fully exploit the potential of engineered timber within the construction sector. Current standards impose 50 years as reference service life for buildings. While irrelevant for traditional materials, which are not carbon stocks, this imposition belittles this unique feature of timber-based materials. Furthermore, current standards for timber-based materials impose well-defined End-of-Life (EoL) scenarios, each culminating with the incineration of the timber – regardless of any cascading process. However, among the possible EoL scenarios, the possibility of reusing engineered timber materials maintaining the same function is not conceived, although technically feasible. Consequently, LCA of buildings following such standards are forced to neglect the potential positive impact of timber-based buildings possibly providing results that tend to favor traditional over timber-based materials. In this work, we show the potential of timber-based buildings to act as a mean of climate mitigation, calling for an urgent modification of the current standard and linked LCA practices. The case study of a timber-based multi-story building shows that RSL extension and reuse reduce the emission by 13% and 1-2% respectively compared to concrete, except for a RSL of 150 years for which the reduction is marginal.